Tinjauan Hukum Islam terhadap Pendistribusian Dana Zakat untuk Kegiatan Produktif dan Kemaslahatan Umum - M. Kasim; Imran Muhammad Yunus; Ilham Thalib (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2022)
This study aims to find out and understand the form of distribution of zakat funds for productive activities and public benefit in the view of Islamic law. The problems that the authors raise in this study are; First, what form is the distribution of zakat funds for productive activities and public benefit? Second, how is the review of Islamic law regarding the distribution of zakat funds for productive activities? Third, how is the review of Islamic law regarding the distribution of zakat funds for public benefit? This research is a qualitative descriptive research (non-statistical), which focuses on the study of manuscripts and texts, using normative and historical approaches and using deductive and comparative analysis methods. The research results found are as follows; The distribution of zakat funds for productive activities is divided into two forms, namely: non-investment and investment. Meanwhile, the form of distribution of zakat funds for the public benefit is that zakat is distributed to other than mustahik mentioned by Allah SWT. such as building bridges, repairing roads, and so on. The distribution of zakat funds is permitted in other forms as needed, productive goods such as goats, razors, etc., as well as in the form of business capital if the distribution is disbursed directly to the mustahik (non-investment).